Anorectal malformations: Early outcome analysis in a tertiary care center in India - Mathew, Priya; Gupta, Arun Kumar; Gupta, Rahul; Sharma, Dharmesh (Journal of Neonatal Surgery, 2021)
Background: Delayed diagnosis, referral, and presence of associated anomalies may influence the outcome of Anorectal malformations (ARM). The aim of this study was to analyze the early outcomes (1 month postoperatively) of ARM presenting in the neonatal period. Methods: A prospective study was carried out in our tertiary care teaching institute from December 2018 to March 2020. All neonates admitted in the NICU with ARM were studied. Results: There were 315 neonates; out of these, 236 (74.92%) were male and 79 (25.07%) were female. High ARM (HARM) was present in 265 (84.13%) and low ARM (LARM) in 50 (15.87%). Associated congenital anomalies were noted in 121 (38.41%). Major associated anomalies consisted of gastrointestinal (GIT) (41.32%), oesophageal (31.4%), and genitourinary (GU) (19.83%). Out of 306 procedures for ARM, 196 (64.05%) neonates underwent left transverse colostomy (LTC). The most frequent postoperative complications were thrombocytopenia (115) followed by sepsis (98). Colostomy prolapse was uncommon (2). The overall mortality was 87/315 (27.61%) neonates - 82/265 (30.94%) in HARM and 5/50 (10%) in LARM. Neonatal mortality was significantly high with birth weight <2500gm 55/153 (35.94%; p value= 0.0001), associated malformations 82 (67.76%, p value= 0.003); and delayed presentation 40/87 (45%), and with primary perforation 5/6 (83.33%). Conclusions: Higher mortality was associated with low birth weight, double/ triple atresia, neonatal GIT perforation, sepsis on admission, and those with oesophageal and cardiac anomalies. More than 1/3rd (38.41%) patients had associated anomalies; thus, a detailed systematic evaluation of all subtypes is paramount.